Pengaruh Rasio Nilai Pasar Dan Kondisi Makro Ekonomi Terhadap Perubahan Harga Saham (Studi Kasus pada Perusahaan Real Estate, Property & Building Construction yang Terdaftar Di Bursa Efek Indonesia Periode 2007-2012) - Pradipsa, Frendita Rukma, Imronudin, S.E, M.Si, Ph.D (2015)
This study, entitled "Effects of the ratio of the value of the market and macro-economic conditions on stock price movements (Case study on real estate companies, property and construction buliding listed in Indonesia Stock Exchange 2007-2012 period)". The purpose of this study was to clarify the effect of the independent variable EPS, PER, PBV, inflation, interest rates and exchange rates on the dependent variable changes in the company's stock price of real estate, property, construction buliding listed on the Indonesia Stock Exchange in 2007-2012 good partially, or simultaneously.The data used in this research is quantitative data using multiple linear regression. Based on t test results of this study can be concluded that in partial EPS and PBV have a significant effect on stock price changes of real estate, property, construction and buliding listed on the Indonesia Stock Exchange, while inflation, interest rates, and exchange rates have no effect Significant to the stock price of property, real estate, construction and buliding listed on the Indonesia Stock Exchange. While test results showed f EPS, PER, PBV, inflation, interest rates, and exchange rates together have a significant effect on stock price changes of real estate, property, and building construction From the calculation results obtained by the coefficient of determination (R2) of 0.598, indicating that the independent variable EPS, PER, PBV, inflation, interest rates, and exchange rates, explain variations in the company's stock price real, estate, property, and building construction by 59 , 8% and the remaining 40.2% is explained by factors or other variables outside the model.